La cartografía de Felipe Guamán Poma de Ayala: El “Mapa Mundi” y las “Ciudades y villas” - Venturi, Fabio (2023)
The “Mapa Mundi del Reino de las Indias” contained in the Primer Nueva Corónica y Buen Gobierno of Felipe Guamán Poma de Ayala constitutes the introductory sheet to the chapter of “Ciudades y villas”. Compared with the contemporary maps of professional cartographers, it is noticeable how implausible the chronicler’s map appears. However, the lack of cartographic technique on the part of Guamán Poma is an irrelevant fact since the intention of the chronicler was to make a synthetic graph of the resources of the viceroyalty of Peru. The “Mapa Mundi” summarizes and complements the chapters of the “Ciudades y villas” and the “Tambos”, which, studied in conjunction with the previous chapter “Preguntas”, constitute an organic unit that, apparently, is connected to the Relaciones Geográficas de Indias, the system that the Spanish authorities implemented to be able to know the new social, cultural, and economic reality that was being formed in the colonies.